An inquiry into the application of biophilic design principles in contemporary university designs - Dilek Yasar; Pınar Öktem Erkartal (Journal of Asian Architecture and Building Engineering)
Environment can have a positive or negative effect on human beings. This effect has been a topic of interest for environmental psychologists, who have strived over the years to understand the environmental attributes, which would be favourable to people in physical, mental, and psychological terms. The present study focusses on biophilic design, one of the popular theories in the architectural literature aimed to create high quality and liveable environments. The positive effects of biophilic design have been investigated from different perspectives and thus it has become a well-accepted approach in the relevant architectural literature. Accordingly, the present study aims to investigate to what extent biophilic design principles were put into practice. In the context thereof, contemporary university structures were analysed within the framework of biophilic design principles. The results suggest that although biophilic elements were present in the design of these structures, they were not specifically intended as biophilic design strategies. Nevertheless, these designs reflected an approach that emphasized human-nature interaction. In that regard, the principles of biophilic design are aligned with key parameters of good design, and architects have regarded nature as a significant design element.